Pediatric Cervicofacial Necrotizing Fasciitis-A Challenge for a Medical Team - Adina Simona Coșarcă; Dániel Száva; Bálint Bögözi; Alina Iacob; Anca Frățilă; Guzun Sergiu (MDPI AG, 2023)
Cervical necrotizing fasciitis is a very rare complication of a bacterial infection that can have a dental cause. This type of infection typically affects fascial plane, which has a poor blood supply and can affect soft tissue and cervical fascia and can spread quickly causing infection of mediastinum. Initially, in the first stage, the overlying tissues are unaffected, and this can delay diagnosis and surgical intervention. Incidence in children is extremely rare and can be frequently associated with various other general pathologies that decrease the immune system response. We present a case of a young 12-year-old boy diagnosed with this type of infection in the head and neck as a complication of a second inferior molar pericoronitis. The treatment and the management of the case was difficult not only due to the presence of the infection but also because of the prolonged intubation.